Oblikovanje in faktorizacija Vprašalnika stališč o športu - Kajtna, Tanja (Psihološka obzorja (Ljubljana), 2008)
Attitudes are lasting cognitive, emotional and conative orientations towards different objects, people, events and occurences, which affect our behaviour. Since a coach plays a cruical role in developing an athlete's career, his attitudes towards different aspects of sport are also important. Because of the absence of adequate instruments for measuring the coach's attitudes, the purpose of this work was to form and factorize an inventory of coach's attitudes towards sport. Inventory of coach's attitudes towards sport initially consisted of 60 items and was applied on 275 Slovene coaches. A scree plot and eigenvalues obtained with the factor analysis have shown a 3-factor solution - we named them education, top sport and problems. The reliability coefficients were well within the range of expected values and we can conclude that the inventory of coach's attitudes towards sport is an adequately reliable instrument. The final version of the instrument contains 40 items.
Keywords: stališča; šport; sport; trenerji; testi; psihologija; psychology